Effect of Reinforcing PMMA Denture Base Material by Stainless Steel 316L Wires on Flexural Strength - Sarmad Ibrahim; Sadeq Lafta; Wafaa Hussain (Journal of Applied Sciences and Nanotechnology, 2023)
A stainless steel 316L (SS316L) wires reinforcing heat cure PMMA matrix samples were prepared for dentures applications. Mechanical scratching and electrochemical anodizing for PMMA denture base supported by wires of SS316L were used as straightforward and low-cost outside layer pretreatments. The two pretreatments were used to improve the flexural strength of PMMA denture bases. The mechanical scratching process acts to scratch the surface of stainless-steel wires by mixing the wires with silicon carbide powder inside a rotating Pyrex container. The pretreatment time was varied to be 60, 90, and 120min. The anodizing solution, containing ethylene glycol (EG) with HClO4 acid, was used with a 15V supply and a graphite rod as a cathode in the anodizing process. A variation in the pretreating time to be 15, 20, and 30min for the electrochemical anodizing process was included. A scanning electron microscope was utilized to examine the morphology of surfaces of the SS316L wires, which showed various morphology natures. The mechanical flexural strength test was conducted for all samples statistically to check the results. The flexural strength test results of the composite sample groups of PMMA reinforced with the scratched surface for 90 min stainless steel wire 316L presented the highest flexural strength value (113 MPa) with a 66% increment. All results proved that reinforcing PMMA by ss 316L are enhancing the flexural strength by comparing the results with previous works and pointing to the activity of the used scratching process.